Improving Clinical Practice: What Dentists Need to Know about the Association between Dental Fear and a History of Sexual Violence Victimisation - Houman Hadad Larijani; Marika Guggisberg (Hindawi Limited, 2015)
Anecdotal evidence suggests lack of dentist knowledge and uncertainty about how clinical practice can be improved when dealing with victims of sexual violence. This systematic review presents a synthesis of the available literature, which examined the association between dental fear and a history of sexual violence victimisation. All studies indicated, to various degrees, that dental fear is associated with a history of sexual violence victimisation. The analysis identified several common themes including a perception of lack of control, avoidance behaviours, experiences of flashbacks, feelings of embarrassment, difficulties with the physical proximity to the dentist, the sex of the dentist reminding patients of the perpetrator, being placed into a horizontal body position, the specific impact of fellatio, the smell of latex, experienced lack of knowledge of dental professionals leading to insensitive treatment as well as revictimisation experiences, and the occurrence of disproportionate dental problems among patients who had experienced event(s) of sexual violence. All these themes are discussed in detail. Specific strategies are offered to assist dental practitioners in providing sensitive treatment for patients with a history of sexual violence. Additionally, several suggestions are made that may assist both researchers and dental practitioners alike.